Prognostic gene alterations and clonal changes in childhood B-ALL. (August 2019) - Erbilgin, Yucel; Firtina, Sinem; Mercan, Sevcan; Hatirnaz Ng, Ozden; Karaman, Serap; Tasar, Orcun; Karakas, Zeynep; Celkan, Tulin Tiraje; Zengin, Emine; Sarper, Nazan; Yildirmak, Zeynep Yildiz; Sisko, Sinem; et al.
Highlights: CDKN2A/2B alterations were the most common variants in diagnosed and relapsed B-ALL. CDKN2A/2B alterations were associated with relapse feature. CRLF2 copy number alterations enriched at non-relapsed B-ALL samples. Early relapsed samples showed a highly dynamic clonal pattern. Abstract: Genomic profiles of leukemia patients lead to characterization of variations that provide the molecular classification of risk groups, prediction of clinical outcome and therapeutic decisions. In this study, we examined the diagnostic (n = 77) and relapsed (n = 31) pediatric B-cell acute lymphoblastic leukemia (B-ALL) samples for the most common leukemia-associated gene variations CRLF2, JAK2, PAX5 and IL7R using deep sequencing and copy number alterations (CNAs) (CDKN2A/2B, PAX5, RB1, BTG1, ETV6, CSF2RA, IL3RA and CRLF2) by multiplex ligation proximity assay (MLPA), and evaluated for the clonal changes through relapse. Single nucleotide variations SNVs were detected in 19% of diagnostic 15.3% of relapse samples. The CNAs were detected in 55% of diagnosed patients; most common affected genes were CDKN2A/2B, PAX5, and CRLF2 . Relapse samples did not accumulate a greater number of CNAs or SNVs than the cohort of diagnostic samples, but the clonal dynamics showed the accumulation/disappearance of specific gene variations explained the course of relapse. The CDKN2A/2B were most frequently altered in relapse samples and 32% of relapse samples carried at least one CNA. Moreover, CDKN2A/2B alterations and/or JAK2 variations were associated with decreased relapse-free survival. On the other hand, CRLF2 copy number alterations predicted a better survival rate in B-ALL. These findings contribute to the knowledge of CDKN2A/2B and CRLF2 alterations and their prognostic value in B-ALL. The integration of genomic data in clinical practice will enable better stratification of ALL patients and allow deeper understanding of the nature of relapse.